LOCAL HERBAL UTILITY IN SUPPORTING SOME PEOPLE HEALTH SUSTAINABILITY - Sirait, Shinta Damerys; Hutasoit, Nicolas M. P. (Journal of Environmental Science and Sustainable Development, 2021)
The efficacy of noni juice (Morinda citrifolia L) for health is very diverse, and has been known for thousands of years. Noni fresh juice contains a relatively high concentration of vitamin C (ascorbic acid) and scopoletin which is known as an important antioxidant and a herbal compound having multy efficasies for health, repectively. Recently, many processed juice products have been widely offered in Indonesia either as medical products or nutritious drinks in liquid and solid forms stored at cold or room temperature for a relatively long period of time, however no one of these products could show the amount of active compound after storage. Vitamin C and scopoletin in noni juice could be changed during storage. This study was aimed at investigating the effects of storage temperature and time on the vitamin C and scopoletin concentration of noni juice. It was conducted at Food Laboratory, AKA Polytechnic Bogor, Indonesia, and the noni juice investigated was packed in plastic containers/cups and stored either at room temperature of 28 oC or in a refrigerator having a temperature of 6oC. The investigation was carried out for 3 (three) parameters i.e pH, vitamin C and scopoletin contents. From data obtained, it can be concluded that there were a decrease of scopoletin and vitamin C concentration remarkably, while pH value was relatively stable (between 4.5 to 6.2) during storage of noni juice, either at room temperature or cold temperature. However, there was still a remarkable amount of scopoletin concentration after 10 weeks of storage (14.21 mg/ liter), that was more than 50 percent of its origin (26,93 mg/liter), fresh noni juice, contrarily vitamin C was almost no more available in the juice after 4 weeks of storage either at room temperature or cold temperature. This vitamin C might not decrease only as a result of oxidation but mostly also because of its proton release and develop a buffer solution, as indicated by the pH stability during storage.